« On n’est jamais tout seul » : étude génétique d’une collaboration Ungaretti–Jaccottet - Patrick Hersant (Carnets)
Philippe Jaccottet translated a number of works by Giuseppe Ungaretti into French, often collaborating with the Italian poet to do so. His work on Ungaretti’s two last poems was luckily archived, so that we can both access the private correspondence between the two translator-poets and examine their translation drafts, all heavily annotated by the Italian poet’s hand. Inspecting the genetic dossier of their brief but intensive collaboration gives us an insight into Ungaretti’s creative process (rewriting, semantic exactness, Italianisms) and Jaccottet’s translative method (initial prose word-for-word, lists of possible choices, distrust of calque).